Competition between uplift and transverse sedimentation in an experimental delta. Issue 7 (15th July 2017) - Grimaud, Jean‐Louis; Paola, Chris; Ellis, Chris
Abstract: Mass is commonly injected into alluvial systems either laterally by transport from source regions or vertically from below via local uplift. We report results on the competition between these two fundamental processes, using an experimental basin with a deformable substrate. The lateral supply is via two alluvial fans on orthogonal walls of the basin; the uplifting region is downstream of one of the fans (axial) and opposite to the other (transverse). We show that the presence of a transverse sediment input increases the erosion rate of the uplifting region by pushing the mixing zone between the two alluvial sources against the uplifting mass. However, increase in sediment delivery to the transverse fan does not cause a proportional increase in erosion rate of the uplifting region. Instead, the system reaches a steady state balance between uplift and erosion induced by the transverse fan, such that there is no change in the total mass above the active alluvial surface—a lateral analog of the classical steady state between vertical erosion and uplift. We also show that the mixing zone is instrumental in limiting upstream aggradation and funneling sediments to the shore, resulting in limited river lateral mobility and increased shoreline progradation. Hence, the interaction between alluvial sources buffers river erosion and leads to consistent deviations from predictions of the area of influence of each fan based on simple mass‐balance arguments. In the Ganges‐Brahmaputra‐Meghna delta, we suggest that similar dynamics help stabilize the Brahmaputra River course in the Jamuna Valley during Holocene time. Key Points: The competition between uplift and transverse sedimentation on river dynamics is studied experimentally Increasing transverse sedimentation does not increase linearly erosion of an uplifting region, which achieves steady‐state above alluvium Buffering of erosion rate is related to the dynamics of the mixing zone between the two alluvial sources